2017
DOI: 10.18517/ijaseit.7.1.1614
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Factors Affecting e-Government Adoption in Indonesia: A Conceptual Framework

Abstract: Electronic government (E-Government) is the use of information and communication technology by the government to increase the service to citizens. E-government also could be applied to the legislative and judicative to improve internal efficiency of democratic governance. However, technological, governing and social issues have to tread carefully in order to adopt these phenomena. This study aims to find critical factor that influences e-government adoption. Furthermore, comprehensive analysis base on the bibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 48 publications
2
26
0
3
Order By: Relevance
“…Furthermore, users also trust the ability and privacy of the technology to perform their transactions. This means the user can strongly trust government initiatives in providing online services to the public [13]- [16]. Table IV, the statistical value t is 3.582, so it can be concluded that PE has significant effect to behavior intention.…”
Section: Fig 2 Structural Model Resultsmentioning
confidence: 81%
“…Furthermore, users also trust the ability and privacy of the technology to perform their transactions. This means the user can strongly trust government initiatives in providing online services to the public [13]- [16]. Table IV, the statistical value t is 3.582, so it can be concluded that PE has significant effect to behavior intention.…”
Section: Fig 2 Structural Model Resultsmentioning
confidence: 81%
“…Trustworthy -It relates to the user's trust to the knowledge base and all the information contained in the application and it became an enabler of decision support system use [26]. In the study of [36], found trusts is a fundamental factor for a user to accept a system. The study is about factors affecting e-government system adoption in Indonesia [36].…”
Section: Fig 4 Remote Envenomation Consultation Mobile Application Umentioning
confidence: 99%
“…In the study of [36], found trusts is a fundamental factor for a user to accept a system. The study is about factors affecting e-government system adoption in Indonesia [36]. With the trust, user will feel comfortable in using it.…”
Section: Fig 4 Remote Envenomation Consultation Mobile Application Umentioning
confidence: 99%
“…It is also recommended to broaden similar studies to e-government service. The experience of users in using previous e-system influences their adoption to the new e-service [30]. Moreover, particularly in a multi-cultural and multi-racial society, the expectation and needs that are developed by the values and norms could be captured by deploying Kansei Engineering technique.…”
Section: Fig 5 Visualization Of the Proposed Train Passenger Seatmentioning
confidence: 99%